Effect of isolation due to COVID-19 on purchasing behavior and brand loyalty in mexicans (Revista de Investigaciones Universidad del Quindío, 2022)
The impact of COVID-19 has been felt immediately, due to the different actions that governments have implemented in their countries, a situation that already persists due to the appearance of different mutations of the virus that has caused serious and profound impacts for almost two years. economic, political, social and psychological, The confinement to which the population has been subjected, has brought with it changes in the behavior of individuals, in the purchase and consumption of products and in brand loyaltyWith the objective of knowing the patterns of purchase and brand loyalty during the confinement caused by the COVID-19 pandemic. A descriptive research with a quantitative approach was carried out on a sample of 1004 subjects, 64% women and 36% men residing in the Mexican Republic, evaluating for this purpose, 3 dimensions regarding consumption: 1) increased consumption, 2) change of brand or change of habits and 3) continuity in the consumption of the same brands (loyalty); all of these, during the contingency of the pandemic; which leads to brand loyalty, considering home, food, medicine, personal care, hygiene and cleaning as essential categories in consumption. As findings we have that there is a global correlation, in all the product categories analyzed with respect to the brands consumed in times of confinement and their continuity after confinement, this situation is not the same in each of the categories evaluated, with the category of cleaning products being the one that shows a greater consumption and lower brand loyalty in this same period
Keywords: Brand loyalty; Buying behavior in COVID-19; Pandemic consumption